2010
DOI: 10.1021/es903337d
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Aromatic Compounds in a Thermal Process Promoted by Oxychlorination of Ferric Chloride

Abstract: The relationship between the formation of chlorinated aromatic (aromatic-Cl) compounds and ferric chloride in the solid phase during a thermal process motivated us to study the chemical characteristics of iron in a model solid sample, a mixture of FeCl(3) x 6H(2)O, activated carbon, and boron nitride, with increasing temperature. Fe K-edge extended X-ray absorption fine structure (EXAFS) spectroscopy revealed drastic changes in the chemical form of amorphous iron, consistent with other analytical methods, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…Dry NaCl, spectrum (A), shows a main absorption peak at 2825.0 eV, corresponding to the transition from 1s to 4p orbitals [55], and a typical post-edge feature [56] at 2836.0 eV. The preedge peak at 2820.8 eV can be attributed to C-Cl bonds [57] due to carbon contamination of the sample, as sizeable amounts of NaOCl, showing an absorption peak at a similar photon energy [58], can be excluded. The NEXAFS spectrum of the frozen NaCl solution (B) is quite different compared to that of the solid phase being characterized by a broader edge with two components.…”
Section: Phase Changes Of Nacl-water Binary Systemsmentioning
confidence: 99%
“…Dry NaCl, spectrum (A), shows a main absorption peak at 2825.0 eV, corresponding to the transition from 1s to 4p orbitals [55], and a typical post-edge feature [56] at 2836.0 eV. The preedge peak at 2820.8 eV can be attributed to C-Cl bonds [57] due to carbon contamination of the sample, as sizeable amounts of NaOCl, showing an absorption peak at a similar photon energy [58], can be excluded. The NEXAFS spectrum of the frozen NaCl solution (B) is quite different compared to that of the solid phase being characterized by a broader edge with two components.…”
Section: Phase Changes Of Nacl-water Binary Systemsmentioning
confidence: 99%
“…The spectra of both reference materials and fly ash were measured to compare their spectral shapes and to identify the major species present. The linear combination fit (LCF) of the XANES spectra has several times been used to identify and quantify major species in particulate matter or incinerator bottom ash (Ressler et al, 2000;Hsiao et al, 2001;Takaoka et al, 2005Takaoka et al, , 2010Fujimori et al, 2010Fujimori et al, , 2011. LCF can determines the proportions of the spectra for selected standards that, when summed, yield the least fit to the spectrum of an unknown sample.…”
Section: Xanes Analysismentioning
confidence: 99%
“…Gullett et al (1992), Oehme et al (1989) and Öberg et al (2007) suggested that nickel compounds could also play a role in the catalytic formation of PCDD/Fs. Recently, X-ray absorption near edge structural (XANES) spectroscopy has been used to monitor redox changes of copper, iron and zinc during dioxin formation (Takaoka et al, 2005Fujimori et al, 2010Fujimori et al, , 2011. This technique will further be used to monitor the speciation of nickel after its reaction in MFA doped with either NiCl 2 or NiO.…”
Section: Introductionmentioning
confidence: 99%
“…In the precursor mechanism there will be the polycondensation of precursor. Usually these gaseous reactions will take place in the range between 300-600 o C. In the de novo synthesis, carbon must be present at the solid phase; on the other hand, the presence of oxygen in the gas phase is also fundamental (Fujimori et al, 2010). Usually these reactions take place at 200-400 o C.…”
Section: Persistent Organic Pollutants From Cement Plantsmentioning
confidence: 99%